1997
DOI: 10.1523/jneurosci.17-06-02040.1997
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Induced Retinal Projections to the Ferret Auditory Thalamus: Development of Clustered Eye-Specific Patterns in a Novel Target

Abstract: We have examined the relative role of afferents and targets in pattern formation using a novel preparation, in which retinal projections in ferrets are induced to innervate the medial geniculate nucleus (MGN). We find that retinal projections to the MGN are arranged in scattered clusters. Clusters arising from the ipsilateral eye are frequently adjacent to, but spatially segregated from, clusters arising from the contralateral eye. Both clustering and eye-specific segregation in the MGN arise as a refinement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 77 publications
2
29
0
Order By: Relevance
“…8 and Table 1). As previously reported (Angelucci et al, 1997), retinal axons were consistently found to ''prefer'' the rostral MGN. Our estimates indicated that approximately 10% of the rostral half of the nucleus receives retinal afferents.…”
Section: Novel Non-retinal Inputs To the Mgn Following Early Extensivsupporting
confidence: 81%
See 1 more Smart Citation
“…8 and Table 1). As previously reported (Angelucci et al, 1997), retinal axons were consistently found to ''prefer'' the rostral MGN. Our estimates indicated that approximately 10% of the rostral half of the nucleus receives retinal afferents.…”
Section: Novel Non-retinal Inputs To the Mgn Following Early Extensivsupporting
confidence: 81%
“…Consistent with this hypothesis, the ''deafferented'' MGN was found to receive some normal inputs from auditory and non-auditory brainstem nuclei spared by the neonatal lesions, as well as novel inputs from the retina and from other sensory nuclei, including somatosensory and visceral nuclei. Support for the hypothesis of competition between afferent axons in the MGN was previously demonstrated by Angelucci et al (1997) who reported that axons from the two eyes segregate into eye-specific clusters in the MGN of experimentally manipulated ferrets. It is conceivable that the undamaged axons innervating the MGN at the time of lesion have a competitive advantage over retinal and other more distantly located axons.…”
Section: Factors Limiting the Extent Of Novel Retinal Projections To mentioning
confidence: 56%
“…1). Under these conditions, retinal axons project to the contralateral medial geniculate nucleus (MGN) and to a lesser extent to the ipsilateral MGN (11,(23)(24)(25)(26).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the dorsal thalamus, specific sets of nuclei receive inputs from defined afferent pathways and become bidirectionally connected with distinct functional areas of the neocortex (Jones, 1985). During these phases afferent activity and competition between innervating fibers play an important role in determining the definitive input-output relationships and the finer grained cytoarchitecture (e.g., Sretevan et al, 1988;Sur et al, 1988;Bhide and Frost, 1992;Angelucci et al, 1997;Penn et al, 1998;Hahm et al, 1999;Stellwagen and Shatz, 2002).…”
mentioning
confidence: 99%